Educational Contribution of Anjman-e-Islamias in India; A Case of Anjman-e-IslamiaAmartasar inthe Social uplift of Muslims in Punjab(1890-1947) - Dr. Sohail Akhtar; Ammara Mushtaq; Tanzeela Mushtaq; Nazia Rahat; Waseem Abbas Gul (Al-Qanṭara, 2022)
The last half of the 19th century is also remarkable for the efforts of the Muslim’s educational organizations for their services to counter the Missionaries activities in Punjab. The research paper is primarily analytical study about the active role of Anjman-e-Islamias especially Anjman-e-Himayatul Islam and Anjman-e-Islamia Amartasar in the promotion of Muslim’s education in Punjab after 1857. The Anjman basically tried to work for the socio-educational development in Punjab with the invasion of Christian Missionaries. The activities of the Missionaries forced the Muslims of Punjab to construct a fence before this religious invasion. Anjman was an organization with multi-dimensional task i.e. education, economy and even politics of the Muslims in Punjab. For the survival of their identity it was a need of the collective and organizational approach to enhance their interest. British introduced new educational system and Muslims were hesitated to follow this which pushed them towards backwardness. The educational decline was in fact their political and their socio-economic decline. Education was an important tool for their political consciousness. On the other hand, the country fellow Hindus adopted the colonial education introduced by East India Company for their prosperity who by virtue adopted this for their educational and politico-economic advancement in India. This step made the Hindus dominant community in Punjab to crush the Muslims due to their illiteracy. Formation of Hindu College played important role among the Hindus for political awareness. The formation of Anjman Islamia Amartasar was to Al-Qantara, Volume, 8, Issue, 4, 2022 25 provide religious and modern education to Muslims children without gender discrimination in Punjab. With this hope Anjman prepared trained scholars and representatives of Muslims confronted the anti-Muslims work and activities of Missionaries in Punjab. Anjman strongly worked for the educational development of the Muslim’s in Punjab and even led in the politics of Punjab during the imperialism. The paper highlights and explores the socio-political contribution of Anjman-eIslamia Amartasar in Punjab. Keywords: Punjab, Muslims, Anjman-e-Islamia, Education, Social, Politics, Amartasar etc.